Inhibition of Rac1-dependent forgetting alleviates memory deficits in animal models of Alzheimer’s disease - Wenjuan Wu; Shuwen Du; Wei Shi; Yunlong Liu; Ying Hu; Zuolei Xie; Xinsheng Yao; Zhenyu Liu; Weiwei Ma; Lin Xu; Chao Ma; Yi Zhong (Protein & Cell, 2019)
Abstract Accelerated forgetting has been identified as a feature of Alzheimer’s disease (AD), but the therapeutic efficacy of the manipulation of biological mechanisms of forgetting has not been assessed in AD animal models. Ras-related C3 botulinum toxin substrate 1 (Rac1), a small GTPase, has been shown to regulate active forgetting in Drosophila and mice. Here, we showed that Rac1 activity is aberrantly elevated in the hippocampal tissues of AD patients and AD animal models. Moreover, amyloid-beta 42 could induce Rac1 activation in cultured cells. The elevation of Rac1 activity not only accelerated 6-hour spatial memory decay in 3-month-old APP/PS1 mice, but also significantly contributed to severe memory loss in aged APP/PS1 mice. A similar age-dependent Rac1 activity-based memory loss was also observed in an AD fly model. Moreover, inhibition of Rac1 activity could ameliorate cognitive defects and synaptic plasticity in AD animal models. Finally, two novel compounds, identified through behavioral screening of a randomly selected pool of brain permeable small molecules for their positive effect in rescuing memory loss in both fly and mouse models, were found to be capable of inhibiting Rac1 activity. Thus, multiple lines of evidence corroborate in supporting the idea that inhibition of Rac1 activity is effective for treating AD-related memory loss.